EVALUATION OF THE NECESSARY LEVEL OF INTERCULTURAL COMPETENCES BASED ON THE ANALYSIS OF THE DIFFERENCE OF CULTURES - Ryabchykova, K. (Problems of Engineer-Pedagogical Education, 2019)
An analysis of the constituents of cultures was carried out to determine the relative importance of intercultural competence in the formation of the international curriculum. The constituent parts of the ethnocultural civilization, the religious group, the level of education, democracy, foreign language proficiency were taken into consideration. A multifunctional semantic analysis was conducted, which allowed to group cultures according to the level of intercultural differences. The paper introduces coefficients of paired intercultural differences as well as the total intercultural coefficient that characterizes the degree of intercultural difference between the two countries or cultures. A study of intercultural differences was made for countries with different religious, civilizational preferences, democratic and educational levels. A relatively small average level of intercultural difference for a number of countries (19.4%) allows realizing the processes of creating intercultural competence on a global scale without significantly changing the curriculum. While developing international curricula, it should be borne in mind that approximately 20% of credit time must be devoted to the formation of intercultural competences.